Morphology, Habitat, Eating Habits and Growth of Tilapia Fish - Galang Pramudya (Academic Letters, 2025)
Tilapia (Oreochromis niloticus) is one type of fish that is widely sought after by the public as a source of animal protein, because its meat is thick and its taste is delicious. In addition, this fish has great potential for cultivation because it is able to adapt to various environmental conditions, including tolerance to a fairly wide range of salinity. This article briefly explains the morphology, habitat, eating habits and growth of tilapia.